2023
DOI: 10.1111/1365-2656.13997
|View full text |Cite
|
Sign up to set email alerts
|

Squamate metabolic rates decrease in winter beyond the effect of temperature

Shahar Dubiner,
Simon Jamison,
Shai Meiri
et al.

Abstract: The reptilian form of hibernation (brumation) is much less studied than its mammalian and insect equivalents. Hibernation and brumation share some basic features but may differ in others. Evidence for hypometabolism in brumating reptiles beyond the effect of temperature is sporadic and often ignored. We calculated the standard metabolic rates (SMR, oxygen uptake during inactivity), in winter and/or summer, of 156 individuals representing 59 species of Israeli squamates across all 17 local families. For 32 spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 105 publications
0
1
0
Order By: Relevance
“…In climates characterized by a strong seasonality, herptiles are inactive during some parts of the year. Throughout these periods of brumation, the level of activity decreases (Dubiner et al, 2023), prolonging various aspects of species’ life history, such as longevity and generation length (Scharf et al, 2015). We found the highest generation length for terrestrial and paedomorphic species, on average, among the life history modes considered.…”
Section: Discussionmentioning
confidence: 99%
“…In climates characterized by a strong seasonality, herptiles are inactive during some parts of the year. Throughout these periods of brumation, the level of activity decreases (Dubiner et al, 2023), prolonging various aspects of species’ life history, such as longevity and generation length (Scharf et al, 2015). We found the highest generation length for terrestrial and paedomorphic species, on average, among the life history modes considered.…”
Section: Discussionmentioning
confidence: 99%
“…We visited each site every 2 months from April 2021 to July 2023, excluding the winter period (December to February) when snakes are rarely found active. Furthermore, many squamate species present a decrease in metabolic rates during winter as part of the brumation process ( Dubiner et al, 2023 ), which would have biased our measurements. For C. polystictus and T. melanogaster , each visit lasted 3 days, during which a team of 2–4 people searched for the snakes in their preferred microhabitats from 10:00 to 18:00 h. As the study site of C. lineata is considerably smaller, sampling occasions for this species were shorter, lasting 1 or 2 days, with a sampling schedule from 10:00 to 14:00 h. For each snake encountered, we registered the time of capture, body mass (g), SVL (mm), sex, and geographic coordinates.…”
Section: Methodsmentioning
confidence: 99%
“…In both experimental procedures, we randomized the sequence of thermal treatments for each individual so that none passed through the treatments in direct ascending or descending order. Since metabolic rates change during rest hours ( Dubiner et al, 2023 ), all tests were performed between 9:00 and 18:00 h, within the observed activity period of the snakes in the field, so that our data accurately represent RMR. Individuals performed only one experimental trial per day to reduce possible confounding effects derived from acute stress.…”
Section: Methodsmentioning
confidence: 99%